MASJID RAYA AL-MASHUN MEDAN: Telaah Sejarah Sosial Keagamaan - Abdul Gani Jamora Nasution; Annida Azhari Ritonga; Annisa Rahmadani; Friska Widya; Miftahul Jannah (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
The purpose of this study is how the history of the Al-Mashun Grand Mosque, the Al-Mashun Grand Mosque in the city of Medan in general has a mixed architectural form. It is divided into three: the main room, used as a place of prayer, the shape of the octagon is not equilateral. The left side (south-east) and the right side (north-east) of the main prayer room are surrounded by alleys (corridors). The shape of the dome follows the shape of Turkish architecture with a broken octagonal shape and an octagonal shaped plan with cylindrical columns at each of the corners of the marble. Research on MASJID RAYA AL- MASHUN MEDAN: A Study of socio-Religious History is relevant by using qualitative research because it meets the characteristics of qualitative research, especially in terms of in-depth data disclosure through interviews, observations and document studies of what informants do, how they carry out activities, what activities are carried out for and why they practice virtue or goodness (good morals) in the real reality.